2016
DOI: 10.1111/pbi.12660
|View full text |Cite
|
Sign up to set email alerts
|

Generation of marker‐free transgenic hexaploid wheat via an Agrobacterium‐mediated co‐transformation strategy in commercial Chinese wheat varieties

Abstract: SummaryGenotype specificity is a big problem lagging the development of efficient hexaploid wheat transformation system. Increasingly, the biosecurity of genetically modified organisms is garnering public attention, so the generation of marker‐free transgenic plants is very important to the eventual potential commercial release of transgenic wheat. In this study, 15 commercial Chinese hexaploid wheat varieties were successfully transformed via an Agrobacterium‐mediated method, with efficiency of up to 37.7%, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
114
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(123 citation statements)
references
References 42 publications
(62 reference statements)
2
114
1
1
Order By: Relevance
“…To study the physiological function of TaDA1 in wheat, we generated TaDA1‐A overexpression lines and RNAi transgenic plants in the hexaploid wheat cultivar Fielder using Agrobacterium ‐mediated transformation (Wang et al , ). The total expression levels of TaDA1 were examined in the transgenic plants using qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To study the physiological function of TaDA1 in wheat, we generated TaDA1‐A overexpression lines and RNAi transgenic plants in the hexaploid wheat cultivar Fielder using Agrobacterium ‐mediated transformation (Wang et al , ). The total expression levels of TaDA1 were examined in the transgenic plants using qRT‐PCR.…”
Section: Resultsmentioning
confidence: 99%
“…For the TaDA1 overexpression construct, the full‐length TaDA1‐A CDS was amplified from Chinese Spring seedling cDNA sample and cloned into the Bam HI and Spe I sites of the pWMB006 vector under the control of the maize ubiquitin promoter Ubi (Wang et al , ). The resulting construct was double‐digested using Hind III and Eco RI, and then cloned into the corresponding sites of the pCAMBIA3301 vector to generate the TaDA1 overexpression construct.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paired‐end (2 × 250) sequencing was conducted with a total of 500 cycles. Sequence analysis was conducted with CRISPR‐DAV (Wang et al ., ) to discover the modification.…”
Section: Methodsmentioning
confidence: 99%
“…In TSI events where the GOI is under the control of the 35S promoter that also drives the expression of the cry2Ae gene from the original cotton event, the double presence of the 35S promoter might have influenced the level of GOI expression in some events. Especially since it has been reported that the 35S sequence is known to be susceptible to silencing by methylation (Okumura et al ., ; Wang et al ., ). However, we believe that another, more general trigger is at play since we observed silencing in TSI events with other GOI promoters while the expression of the 35S driven cry2Ae gene was stable and not affected in any of the plants tested.…”
Section: Discussionmentioning
confidence: 97%